(untitled) (SigMe, 2025)
During the 2023–2024 dengue epidemic outbreak in Argentina, neurological manifestations associated with the infection were observed with increasing frequency, which prompted this study at Hospital J.M. Cullen, Santa Fe. A retrospective, descriptive analysis was conducted on patients who were hospitalized with confirmed dengue and neurological complications between November 2023 and May 2024. Eighteen cases were analyzed. Complications were central in 77.8 % and peripheral in 22.2 % of the cases. The most frequent were Guillain-Barré syndrome, seizures, and ischemic stroke. Fifty per cent (50%) of the patients required intensive care. The mortality rate was 5.6 %, and one-third required rehabilitation. The findings are consistent with regional studies and show that dengue can present with neurological involvement of varying severity.